Prognostic value of sST2 and galectin-3 for death relative to renal function in patients hospitalized for heart failure. (May 2015) - Zhang, Rongcheng; Zhang, Yuhui; An, Tao; Guo, Xiao; Yin, Shijie; Wang, Yunhong; Januzzi, James L; Cappola, Thomas P; Zhang, Jian
Aim: To evaluate the associations of soluble ST2 (sST2) and galectin-3 with death relative to renal function in patients with heart failure (HF).Methods: Eleven-hundred-and-sixty-one patients hospitalized for HF with 1-year follow up were enrolled for biomarkers analysis.Results: Patients were divided into two groups based on eGFR of either > or ≤60 ml/min/1.73 m 2 . sST2 was independently associated with death in both categories of renal function, while galectin-3 lost this significance after addition of NT-proBNP to the model of patients with eGFR ≤60 ml/min/1.73 m 2 .Conclusion: In patients with HF, sST2 improved prediction for death beyond risk factors without being influenced by renal function, however, the prognostic value of galectin-3 is less clear below an eGFR of 60 ml/min/1.73 m 2 .